Structural, electro-magnetic, and optical properties of Ba(Fe, Ni)2As2 single-crystal thin film. (29th December 2016) - Yoon, Sejun; Seo, Yu-Seong; Lee, Seokbae; Weiss, Jeremy D; Jiang, Jianyi; Oh, MyeongJun; Lee, Jongmin; Seo, Sehun; Jo, Youn Jung; Hellstrom, Eric E; Hwang, Jungseek; Lee, Sanghan
Abstract: We investigated the superconducting transition temperature ( T c ), critical current density ( J c ) and optical properties of optimally doped Ba(Fe0.95 Ni0.05 )2 As2 (Ni-Ba122) single-crystalline epitaxial thin films grown by pulsed laser deposition for the first time. The T c at zero resistivity was about 20.5 K and the J c at self-field and 4.2 K was 2.8 MA cm −2 calculated by the Bean model. The superconducting properties such as T c and J c of thin films are comparable to those of bulk single-crystal samples. The superfluid plasma frequency ( λ p, S ) of Ni-Ba122 thin film is ∼7033 cm −1 obtained by optical spectroscopic technique. Based on this plasma frequency, we obtained the London penetration depth ( λ L ), ∼226 nm at 8 K, which is comparable to those of optimally Co- and K-doped BaFe2 As2 single crystals.